1997
DOI: 10.1159/000139507
|View full text |Cite
|
Sign up to set email alerts
|

Activation of IMeuronal Nitric Oxide Synthase by M2 Muscarinic Receptors Associated with a Small Increase in Intracellular Calcium

Abstract: We investigated the coupling of the M2 muscarinic acetylcholine receptors expressed in Chinese hamster ovary cells to activation of neuronal nitric oxide (NO) synthase. Stimulation of guanylate cyclase activity in detector neuroblastoma cells was used as an indirect measure of the generation of NO in Chinese hamster ovary cells. The muscarinic agonist carbachol induced marked time- and concentration-dependent enhancement of the activity of NO synthase. Activation of neuronal NO synthase by M2 muscarinic recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It remains unclear how M 2 and M 4 receptors couple to increased levels of intracellular free Ca 2+ , since we were unable to detect increased phosphoinositide hydrolysis upon activation of either M 2 or M 4 receptors (data not shown). This confirms previous findings [20].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It remains unclear how M 2 and M 4 receptors couple to increased levels of intracellular free Ca 2+ , since we were unable to detect increased phosphoinositide hydrolysis upon activation of either M 2 or M 4 receptors (data not shown). This confirms previous findings [20].…”
Section: Discussionsupporting
confidence: 94%
“…While chelating extracellular Ca 2+ expectedly eliminated the sustained cGMP response, it also greatly decreased the peak cGMP response. This suggests that extracellular Ca 2+ ifnlux plays a major role in eNOS activation, different from the mechanism of activation of nNOS by M 2 receptors [20]. It remains unclear how M 2 and M 4 receptors couple to increased levels of intracellular free Ca 2+ , since we were unable to detect increased phosphoinositide hydrolysis upon activation of either M 2 or M 4 receptors (data not shown).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, M2 receptors have been reported to activate low levels of PLC activity (Ashkenazi et al, 1987), and production of NO by M2 mAChRs has been reported in transfected Chinese hamster ovary (CHO) cells. Although no mechanism was definitively elucidated, the effects were thought to be the result of the release of intracellular calcium, not an influx of extracellular calcium (Wang et al, 1997). It is therefore very likely that the M2 muscarinic receptors expressed in the salamander retina could lead to modulation of other signaling pathways by NO.…”
Section: Ach and Nomentioning
confidence: 99%
“…Our laboratory has been involved in investigating the relationship between muscarinic receptor-mediated Ca2~signaling and nNOS activation (Surichamorn et al, 1990;Wang et al, 1996Wang et al, , 1997. It is interesting that the kinetics of nNOS activation by muscarinic Neuronal nitric oxide (NO) synthase (nNOS) rapidly metabolizes L-arginine into NO and L-citrulline on stimulation (Bredt, 1995).…”
mentioning
confidence: 99%